Natural occurrence of ochratoxin A (OTA) in edible and not edible tissue of farmed gilthead seabream (Sparus aurata) and European seabass (Dicentrarchus labrax) sold on the Italian market. (February 2021) - Meucci, Valentina; Armani, Andrea; Tinacci, Lara; Guardone, Lisa; Battaglia, Federica; Intorre, Luigi
Abstract: Ochratoxin A (OTA) is a mycotoxin produced as secondary metabolite by various Aspergillus and Penicillium species, with ascertained nephrotoxic, immunotoxic, carcinogenic and teratogenic potential. As a result of the introduction of alternative vegetable sources to substitute fish meal and fish oil, OTA may also contaminate aquafeed. This represents a potential issue for consumers' safety, due to the possible transmission and accumulation in animal edible tissues by carry over. The present study aimed at assessing natural OTA occurrence in edible (muscle) and not edible tissue (liver and kidney) of farmed gilthead seabream ( Sparus aurata ) and European seabass ( Dicentrarchus labrax ) sold on the Italian market in order to evaluate their possible contribution to human exposure and consequent public health risk. Target tissue samples belonging to 30 farmed gilthead seabream and 30 farmed European seabass were analysed by means of HPLC-FT validated method. The analysis highlighted the presence of OTA residues above the minimum detection limit in edible (mean LOD 0.12 ± 0.11 μg/kg) and not edible tissue (kidney mean LOD 0.32 ± 0.30 μg/kg, and liver mean LOD 0.53 ± 0.22 μg/kg) without significant differences between the two species. The investigation of commercial samples and the detection of OTA residues in muscle represents a novelty compared to previous studies evaluating the occurrence of OTA in fish species. Overall, outcomes of this study suggest the need to evaluate a further broadening of the basket of potentially implicated food sources of animal origin in the OTA exposure risk, also considering that for fish and seafood no OTA residual limits have yet been proposed. Highlights: Natural OTA occurrence was assessed in two commercial fish species. 60 farmed gilthead seabream and European seabass were analysed by validated HPLC-FT method. OTA residues above the minimum detection limit were found in muscle, kidney and liver. No significant differences were observed between the two species. Broadening the basket of potentially implicated food sources should be considered.